2019
DOI: 10.1523/jneurosci.3014-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing Increased miR-135a Levels at the Chronic Stage of Experimental TLE Reduces Spontaneous Recurrent Seizures

Abstract: Mesial temporal lobe epilepsy (mTLE) is a chronic neurological disease characterized by recurrent seizures. The antiepileptic drugs currently available to treat mTLE are ineffective in one-third of patients and lack disease-modifying effects. miRNAs, a class of small noncoding RNAs which control gene expression at the post-transcriptional level, play a key role in the pathogenesis of mTLE and other epilepsies. Although manipulationofmiRNAsatacutestageshasbeenreportedtoreducesubsequentspontaneousseizures,itisun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 80 publications
(112 reference statements)
1
29
0
Order By: Relevance
“…S1 A and B). Next, additional mice were subjected to IAKA and then monitored over the next 2 wk for spontaneous recurrent seizures (SRSs) (29,31). After establishing equivalent baseline rates of SRSs (SI Appendix, Fig.…”
Section: Ago2 Sequencing Provides a Quantitative Catalog Of Functionallymentioning
confidence: 99%
“…S1 A and B). Next, additional mice were subjected to IAKA and then monitored over the next 2 wk for spontaneous recurrent seizures (SRSs) (29,31). After establishing equivalent baseline rates of SRSs (SI Appendix, Fig.…”
Section: Ago2 Sequencing Provides a Quantitative Catalog Of Functionallymentioning
confidence: 99%
“…In TLE patients, miR‐135a expression is upregulated 14,40 . Furthermore, mechanistic studies in the kainic acid–induced mouse epilepsy model showed that miR‐135a downregulation using antagomirs after the onset of spontaneous seizures reduced the number of spontaneous seizures per day and the seizure count and duration by targeting hippocampal myocyte enhancer factor 2A (mef2a), 41 suggesting that miR‐135a has the potential to modify epileptogenesis. MEF2A, as a transcription factor that is highly expressed in hippocampal CA1 neurons, 42 suppresses excitatory synapse number in hippocampal neurons 43 ; however, the effects of miR‐135a on epileptogenesis require further clarification 5 .…”
Section: Mir‐135amentioning
confidence: 99%
“…Non-radioactive in situ hybridization (ISH) was performed as described previously 64 . Except, hybridization was performed with 10 nM of double-DIG (3’ and 5’) - labelled locked nucleic acid (LNA) probes for miR-10a-5p, miR-142a-5p, miR-21a-5p and LNA-DIG Scramble probe (Exiqon) overnight at 50 °C followed by stringency washes at 55 °C.…”
Section: Methodsmentioning
confidence: 99%